2023
DOI: 10.1186/s42523-023-00230-2
|View full text |Cite
|
Sign up to set email alerts
|

Omics and imaging combinatorial approach reveals butyrate-induced inflammatory effects in the zebrafish gut

Abstract: Background Prebiotic feed additives aim to improve gut health by influencing the microbiota and the gut barrier. Most studies on feed additives concentrate on one or two (monodisciplinary) outcome parameters, such as immunity, growth, microbiota or intestinal architecture. A combinatorial and comprehensive approach to disclose the complex and multifaceted effects of feed additives is needed to understand their underlying mechanisms before making health benefit claims. Here, we used juvenile zeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Contrarily, in sea bass, supplementation of butyrate in the diet is reported to increase the expression of TNF-alpha in the intestines and promote the turnover of cells within the intestinal crypts [25]. This variation in the expression of TNF-alpha in response to butyrate could be due to the fact that butyrate is not known to be naturally occurring within the zebrafish gut [26]. Moreover, LPS was not used to elicit an inflammatory response within the sea bass but rather a soybean meal diet [25].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, in sea bass, supplementation of butyrate in the diet is reported to increase the expression of TNF-alpha in the intestines and promote the turnover of cells within the intestinal crypts [25]. This variation in the expression of TNF-alpha in response to butyrate could be due to the fact that butyrate is not known to be naturally occurring within the zebrafish gut [26]. Moreover, LPS was not used to elicit an inflammatory response within the sea bass but rather a soybean meal diet [25].…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate also inhibits histone deacetylase 3 (HDAC3) involved in chromatin remodeling and produces epigenetic changes [ 53 ] that modify the cell fate of immune cells. In fish, butyrate has been identified in the gut of carnivorous and herbivorous specimens [ 54 , 55 ], promotes the expression of heat shock protein HSP70, pro-inflammatory factors (IL-1β and TNF-α), and anti-inflammatory cytokines (TGF-β) in Cyprinus carpio [ 56 ], and improves the inflammatory response in juvenile zebra fish [ 57 ]. Butyrate has been detected in the intestinal feces of Atlantic salmon at a concentration of around 1 mM [ 58 , 59 ].…”
Section: Probioticsmentioning
confidence: 99%
“…This was consistent with another study that found that pre-treatment with butyrate increased survival and decreased production of TNF-α following exposure to LPS in 3 dpf larvae ( Wang, 2023 ). Noteworthy, a recent high throughput quantitative histological and transcriptomic analyses of the zebrafish gut showed that sodium butyrate supplemented in feed increased the expression of pro-inflammatory genes and activity of oxidoreductase, decreased expression of genes involved in histone modification, mitotic process, GPCR activity, and increased relative abundance of Rhodobacter , Flavobacterium and Bacteroides, which are associated with inflammation in juvenile zebrafish gut ( López Nadal et al, 2023 ). Histological analysis also showed that butyrate supplementation increased eosinophils, rodlet cells and reduced mucus producing cells in the gut ( López Nadal et al, 2023 ), suggesting the responsiveness of the zebrafish gut immune system to the changes in the gut microbiota.…”
Section: Utilizing the Zebrafish Microbiome As A Functional Biomarker...mentioning
confidence: 99%
“…Noteworthy, a recent high throughput quantitative histological and transcriptomic analyses of the zebrafish gut showed that sodium butyrate supplemented in feed increased the expression of pro-inflammatory genes and activity of oxidoreductase, decreased expression of genes involved in histone modification, mitotic process, GPCR activity, and increased relative abundance of Rhodobacter , Flavobacterium and Bacteroides, which are associated with inflammation in juvenile zebrafish gut ( López Nadal et al, 2023 ). Histological analysis also showed that butyrate supplementation increased eosinophils, rodlet cells and reduced mucus producing cells in the gut ( López Nadal et al, 2023 ), suggesting the responsiveness of the zebrafish gut immune system to the changes in the gut microbiota. Moreover, Morales Fenero et al showed that SCFA can increase survival rate, reduce expression of inflammatory cytokines, and reduce the recruitment of neutrophils in a colitis model induced by 2,4,6-trinitrobenzene sulfonic acid in larval zebrafish ( Morales Fénero et al, 2021 ).…”
Section: Utilizing the Zebrafish Microbiome As A Functional Biomarker...mentioning
confidence: 99%